Effects of IKur blocker MK-0448 on human right atrial action potentials from patients in sinus rhythm and in permanent atrial fibrillation - Loose, Simone; Mueller, Judith; Wettwer, Erich; Knaut, Michael; Ford, John; Milnes, James; Ravens, Ursula (Frontiers in Pharmacology, 2014)
Selective blockers of the Kv1.5 channel have been developed for the treatment of atrial fibrillation (AF), but little is known how these atrial-selective drugs affect human action potentials (APs). Therefore we have investigated the Kv1.5 blocker MK-0448 (N-{6-[(1S)-1-(4-fluorophenyl)-2,2-di(pyridin-3-yl)ethyl]pyridin-2-yl}methanesulfonamide) in right atrial trabeculae from patients in sinus rhythm (SR), permanent AF (> 6 months), and intermittent AF. MK-0448 blocked Kv1.5 current in an expression system and concentration-dependently elevated the plateau phase of atrial APs. In SR preparations stimulated at 1 Hz, MK-0448 (3 µM) shortened action potential duration at 90% of repolarization (APD90) and effective refractory period (ERP), but in permanent AF preparations, MK-0448 prolonged APD90 and ERP. The effects of MK-0448 in intermittent AF resembled those in SR preparations. The APD-prolonging effect in AF preparations was more pronounced than with other IKur blockers, most likely due to the additional blocking effect of MK-0448 on IKs, a current that is present both in the atrium and ventricle. Block of IKs is probably more prominent in AF because of reduced repolarization reserve due to AF-induced remodeling.